Alkaloidal Root Extract Of Nauclea Latifolia (Rubiaceae) Inhibited Induced Acute And Chronic Inflammations In Wistar Rats - S. Ajala, Olusegun; L. Ekeanyanwu, Ogechi; L. Eze, Chioma (The Nigerian Journal of Pharmacy, 2018)
Background: The Plethora of adverse reactions associated with the long-term use of most Non-Steroidal Anti-inflammatory Drugs (NSAIDs) are not unconnected to their prostaglandin biosynthesis inhibition mechanism of action. NSAIDs of alternative mechanism of action could therefore be better substitutes. Indole alkaloids are both biogenetically and structurally related to serotonin, an alternative inflammation mediator, and are therefore a possible chemical repertoire explorable for the discovery of new NSAIDs. The present research was aimed at evaluating an alkaloidal root extract of an indolealkaloid-rich plant, Nauclea latifolia (Rubiaceae), for its potential inhibitory activities on acute and chronic inflammations, for an ultimate possible discovery of such indole-based NSAIDs. Methods: Alkaloidal components of a crude methanol extract of Nauclea latifolia root was obtained by acid-base treatment and concentrated to dryness. Effects of the alkaloidal extract on acute inflammation was evaluated in vivo in a carrageenan-induced paw edema rat model, measuring edema size at 30min intervals over a 3hr time-course, while a cotton pellet-induced granuloma rat model was used to evaluate effects of the extract on chronic inflammation. Results: The extract significantly reduced the induced edema to varying degrees compared to the negative control (p <0.05, 0.01, 0.001 and 0.0001) over the 3hr time-course of observation, producing a maximum % inhibition (41.97%) 3hrs after induction. It also significantly inhibited the development of the cotton-pellet induced granuloma after seven days compared to the negative control (p < 0.05), in the chronic inflammation experiment. Conclusion The results show that alkaloids of Nauclea latifolia have anti-inflammatory activities and could therefore be explored as templates in the discovery of new anti-inflammatory agents.